STABILITY OF SILAGE MADE CATFISH WASTE WITH THE BACKSLOPPING FERMENTATION METHOD DURING STORAGE - Indra Anggraini; Bustari Hasan; Syahrul Syahrul (Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
This study was purpose to evaluate the stability of pH, NPN and proximate value of catfish waste silage made by adding the backslop method inoculum during storage. The experimental design used was a randomized block design (RAK), as the treatment was silage without inoculum and silage added inoculum, while silage storage was as a group (0,7,15 and 21). The parameters evaluated were pH, NPN and proximate. The results showed that the pH of the silage with the addition of an inoculum and without an inoculum was relatively stable because it was at pH 4. Statistical analysis showed that the average pH value of the inoculum added silage was lower than the inoculum silage and was not significantly different (p> 0.05). Statistical analysis showed that the average value of NPN with inoculum added silage was lower than that of silage without inoculum. Silage without inoculum and silage inoculum on day 7, 15 and 21 were significantly different (p> 0.05) while on day 0 they were not significantly different (p> 0.05). High proximate silage content is found in silage added with inoculum with a water content value of 66.60%, ash 1.49%, protein 20.60%, fat 3.02%.